(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Today, more than ever before, the world has become a small cosmopolitan village as a result of the information, communication and communication revolution that humanity is witnessing under a globalized capitalist system that has turned itself into passive peripheries and active centers. In the context of the existing global capitalist polarization, peripheral countries suffer from double backwardness; they are both technologically and structurally backward. Thus, find themselves faced with the challenge of this complex backwardness, both in the field of productive forces and in the field of relations of production. The challenge of underdevelopment, in the first field, requires engagement in world system centers through capitalist market mechanisms, prevalent there and at the global level. In addition, the challenge of backwardness, in the second field, requires disengagement with these centers in order to build new non-capitalist relations of production, as a structural condition necessary to ensure the development of productive forces with local resources and competences. This will soon lead to the disconnection of dependency linkages, and thus national control over the engagement itself. Hence, the engagement is a necessary element for disengagement, which does not mean autarchic, in any case. As a result, logically and objectively, the dialectics of engagement and disengagement are connected organically to the dialectics of market and planning, in a way that is related to the need of developing the productive forces and building the productive relations with a different essence.